2006
DOI: 10.1152/ajpregu.00148.2006
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hypoglycemia reduces the glucose sensitivity of glucose-inhibited neurons in the ventromedial hypothalamus nucleus

Abstract: Recurrent hypoglycemia blunts the brain's ability to sense and respond to subsequent hypoglycemic episodes. Glucose-sensing neurons in the ventromedial hypothalamus nucleus (VMN) are well situated to play a role in hypoglycemia detection. VMN glucose-inhibited (GI) neurons, which decrease their firing rate as extracellular glucose increases, are extremely sensitive to decreased extracellular glucose. We hypothesize that recurrent hypoglycemia decreases the glucose sensitivity of VMN GI neurons. To test our hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 22 publications
10
98
1
Order By: Relevance
“…The present studies also differ in other respects from the only other study in which VMH glucosensing neurons were examined after recurrent bouts of IIH (49). The previous study (49) demonstrated that VMN GI neurons from recurrently hypoglycemic rats failed to respond at 0.5 mmol/l glucose but did respond at 0.1 mmol/l, suggesting that recurrent hypogly- A total of 3,786 neurons from saline-or insulin-treated rats (VMN from 642 saline-and 800 insulin-treated rats and ARC from 1,442 saline-and 902 insulin-treated rats) were classified as glucose excited (GE) or glucose inhibited (GI) by their changes in area under the curve of intracellular Ca 2ϩ concentration (͓Ca 2ϩ ͔i) when glucose was lowered from 2.5 to 0.1 mmol/l glucose.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The present studies also differ in other respects from the only other study in which VMH glucosensing neurons were examined after recurrent bouts of IIH (49). The previous study (49) demonstrated that VMN GI neurons from recurrently hypoglycemic rats failed to respond at 0.5 mmol/l glucose but did respond at 0.1 mmol/l, suggesting that recurrent hypogly- A total of 3,786 neurons from saline-or insulin-treated rats (VMN from 642 saline-and 800 insulin-treated rats and ARC from 1,442 saline-and 902 insulin-treated rats) were classified as glucose excited (GE) or glucose inhibited (GI) by their changes in area under the curve of intracellular Ca 2ϩ concentration (͓Ca 2ϩ ͔i) when glucose was lowered from 2.5 to 0.1 mmol/l glucose.…”
Section: Discussioncontrasting
confidence: 73%
“…A previous study in 2-to 3-wk-old rat pups showed that the development of a dampened AMR after three bouts of IIH was associated with a reduced responsiveness of VMN GI neurons to glucose (49). However, little is known about the actual mechanisms underlying such alterations in neuronal glucosensing and whether they occur in VMN GE neurons or other neurons outside the VMN.…”
mentioning
confidence: 98%
“…Lactate is known to reduce glucose sensitivity in glucoseinhibited neurons of suckling rats (Song and Routh, 2006), and brain of suckling rats can use lactate as fuel (Song and Routh, 2006) in a way similar to that of fish brain (Soengas et al, 1998). We have demonstrated in previous studies the existence of glucosensing mechanisms in hypothalamus, hindbrain and BB of rainbow trout (Soengas et al, 2006;Polakof et al, 2007a;Polakof et al, 2007b).…”
Section: Introductionmentioning
confidence: 83%
“…There is mounting evidence that changes in pathways that regulate energy metabolism are incurred from exposure to dysregulated metabolic environments such as during diabetes, obesity or hypoglycemia (Sango, et al, 1991;Sango, et al, 1994;Cryer, 2001;Chen, et al, 2005;Song, et al, 2006;Martin, et al, 2006;Somoza, et al, 2007). In states of disrupted energy balance animals respond differently to known modulators of neuronal metabolism.…”
Section: Discussionmentioning
confidence: 99%